2010
DOI: 10.1111/j.1742-7843.2009.00500.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased Hepatic and Decreased Urinary Metallothionein in Rats after Cessation of Oral Cadmium Exposure

Abstract: Abstract:We investigated the role of metallothionein (MT) in tissues after cessation of cadmium (Cd) exposure. Wistar rats of both genders were given CdCl 2 in drinking water at daily doses of 0, 2.5, 5.0 or 10.0 mg Cd ⁄ kg body-weight for 12 weeks. Half of the animals were then killed; the others were given Cd-free water for the following 16 weeks, i.e. until 28 weeks after start of the experiment (28-week rats). We observed dose-dependent increases in the levels of MT in the tissues of rats 12 weeks after be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Because of NAG’s direct relevance to the integrity of proximal tubular cells, the release of NAG into the urine is an early sign of tubular membrane damage (Bernard et al 1995; Jin et al 1999). In addition, our recent animal study (Liang et al 2010) confirmed increased hepatic and decreased urinary metallothioneins (a family of 6- to 7-kDa stress proteins incorporating a high content of cysteine and divalent metals) after cessation of oral Cd exposure, suggesting that urinary metallothionein could be another informative marker to evaluate recovery of Cd-mediated renal tubular dysfunction after a reduction in exposure.…”
Section: Discussionmentioning
confidence: 75%
“…Because of NAG’s direct relevance to the integrity of proximal tubular cells, the release of NAG into the urine is an early sign of tubular membrane damage (Bernard et al 1995; Jin et al 1999). In addition, our recent animal study (Liang et al 2010) confirmed increased hepatic and decreased urinary metallothioneins (a family of 6- to 7-kDa stress proteins incorporating a high content of cysteine and divalent metals) after cessation of oral Cd exposure, suggesting that urinary metallothionein could be another informative marker to evaluate recovery of Cd-mediated renal tubular dysfunction after a reduction in exposure.…”
Section: Discussionmentioning
confidence: 75%
“…It has been shown that Cd ean target a number of tissues in eukaryotic organisms and induce oxidative damage by disturbing the prooxidant-antioxidant balance [2]. Exposure of an organism to Cd initiates the cellular defense mechanism by up-regulating the synthesis of metal-hinding proteins known as metallothioneins (MTs) [4]. Exposure of an organism to Cd initiates the cellular defense mechanism by up-regulating the synthesis of metal-hinding proteins known as metallothioneins (MTs) [4].…”
Section: Introductionmentioning
confidence: 99%
“…Long-term Cd exposure has been reported, and renal dysfunction has already been proven [45,46]. Uβ 2 -MG and UNAG are in use as biomarkers for clinical diagnosis [15,21] and animal experiments [47,48]. In the later stages of Cd-induced renal injury, the tubular epithelial cells may shrink, fall off, and even disappear, and the tissue source of UNAG is lost [49].…”
Section: Discussionmentioning
confidence: 99%